Physics-Inspired Optimization Algorithms: A Survey. (12th June 2013) - Biswas, Anupam; Mishra, K. K.; Tiwari, Shailesh; Misra, A. K.
Abstract : Natural phenomenon can be used to solve complex optimization problems with its excellent facts, functions, and phenomenon. In this paper, a survey on physics-based algorithm is done to show how these inspirations led to the solution of well-known optimization problem. The survey is focused on inspirations that are originated from physics, their formulation into solutions, and their evolution with time. Comparative studies of these noble algorithms along with their variety of applications have been done throughout this paper.